Philonic exegesis in Gregory of Nyssa's De vita Moysis - Geljon, Albert C. (Brown judaic studies, 2002)
The place of Philo's De vita Moysis within his œuvre -- Gregory and his De vita Moysis -- The philonic background of Gregory's De vita Moysis